Метацеркарии дигенетических трематод бентических членистоногих водоемов дельты Дуная - Комарова, Т.И. (Вестник зоологии, 1968)
The article deals with the description of morphological structure and drawings of metacercaria of digenetic trematodas, which were found in the benthic Arthropoda from the basins of the Danube delta. The life cycle of such trematodas as Crowcrocoecum skrjabini, Skrjabinopsolus skrlabini, Pleurogenes medians, P. claviger is exposed partially.